2000
DOI: 10.1016/s0370-2693(00)00316-6
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb corrections to elastic electron–proton scattering and the proton charge radius

Abstract: Recent values of the proton charge radius derived from the Lamb shift in electronic hydrogen tend to be larger than those from electron scattering. Therefore low-momentum-transfer scattering data from different groups and laboratories have been reanalyzed with Coulomb and recoil corrections included. This was done by calculating at each scattering angle and scattering energy the corresponding correction obtained from a partial wave program which includes recoil approximately. Corrections due to magnetic scatte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
117
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 21 publications
15
117
0
Order By: Relevance
“…Rinker(1976) [217] Borie, Rinker(1978) [218] [211,212] 0.0232 (15) Faustov,Martynenko(1999) [168] Nuclear structure correction of order (Zα) 5 Startsev,Petrun'kin, Khomkin(1976) [172] Rosenfelder(1999) [159] Faustov,Martynenko(1999) [168] Pachucki(1999) [212] − 0.095 (18) n 3 δ l0 0.012 (2) Nuclear size correction of order (Zα) 6 Borisoglebsky, Trofimenko(1979) [164] Friar(1979) [165] − < ln The theory of the atomic energy levels developed in the previous sections is incomplete, since we systematically ignored the nuclear spin which leads to an additional splitting of the energy levels. This effect will be the subject of our discussion below.…”
Section: Fig 63 Electron Polarization Corrections To the Leading Numentioning
confidence: 99%
See 2 more Smart Citations
“…Rinker(1976) [217] Borie, Rinker(1978) [218] [211,212] 0.0232 (15) Faustov,Martynenko(1999) [168] Nuclear structure correction of order (Zα) 5 Startsev,Petrun'kin, Khomkin(1976) [172] Rosenfelder(1999) [159] Faustov,Martynenko(1999) [168] Pachucki(1999) [212] − 0.095 (18) n 3 δ l0 0.012 (2) Nuclear size correction of order (Zα) 6 Borisoglebsky, Trofimenko(1979) [164] Friar(1979) [165] − < ln The theory of the atomic energy levels developed in the previous sections is incomplete, since we systematically ignored the nuclear spin which leads to an additional splitting of the energy levels. This effect will be the subject of our discussion below.…”
Section: Fig 63 Electron Polarization Corrections To the Leading Numentioning
confidence: 99%
“…A new analysis of the low momentum transfer electron scattering data with account of the Coulomb and recoil corrections [159] resulted in the proton radius value r p = 0.880 (15) fm,…”
Section: Comparison Of Theory and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have argued (see, e.g., [63,65]) that the Hand et al result is not credible as it was based on a Q2 X 0 extrapolation of the dipole form factor fitted to high Q 2 data.…”
Section: Proton Charge Radiusmentioning
confidence: 99%
“…Using a method analogous to that employed by Ernst, Sachs, and Wali [17] and Sachs [18] for a physical interpretation of the nucleon form factors, Gourdin [73] showed that the following linear combinations of F 0 , F 2 , and G 1 , 63) GM -GI (2.64) are related to the distributions of the deuteron's charge (C), quadrupole moment (Q), and magnetic moment (M) in the Breit frame. Further, Gourdin showed that The difficulties associated with an extraction of GEn from A(Q 2 ) are as follows.…”
Section: Neutron Form Factors Via Unpolarized Quasielasticmentioning
confidence: 99%